2018
DOI: 10.4034/pboci.2018.181.13
|View full text |Cite
|
Sign up to set email alerts
|

Perceived and Normative Needs of Facial Cleft Patients Seen in Nigeria

Abstract: Objective: To evaluate the pattern of presentation and assessing treatment needs of children with facial clefts. Material and Methods: This was a cross sectional study of 49 patients seen at the cleft clinic of Obafemi Awolowo University Teaching Hospitals Complex, Ile-Ife for a 39-month period of study. Data collected were patient's bio-data including age, date of birth, sex, social class, age of parents, dental findings, associated malformations, treatment given and referral using an interviewer-administered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In this study, higher prevalence of cleft lip and palate was observed in male children, a result similar to that reported by other authors 6,9,13-15 . Some authors report that the palate merges later in female children, contributing to increase the occurrence of this condition in this population group 16,17 . Research with Taiwanese children demonstrated a higher prevalence of cleft lip with or without cleft palate (CL/P) among boys and cleft palate (CP) among girls 18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, higher prevalence of cleft lip and palate was observed in male children, a result similar to that reported by other authors 6,9,13-15 . Some authors report that the palate merges later in female children, contributing to increase the occurrence of this condition in this population group 16,17 . Research with Taiwanese children demonstrated a higher prevalence of cleft lip with or without cleft palate (CL/P) among boys and cleft palate (CP) among girls 18 .…”
Section: Discussionmentioning
confidence: 99%
“…This homogeneity and absence of large increases over time may suggest that environmental factors have little influence on the occurrence of these changes. The presence of this condition may negatively influence the quality of life of individuals, causing important psychological and functional disorders 25 , in addition to unfavorably influencing the oral health quality of patients affected 7,15,17,26 , vocal resonance 27 , aesthetics 22 , among other factors.…”
Section: Discussionmentioning
confidence: 99%
“…To treat these patients, a multidisciplinary approach is necessary, with follow-up of physicians, dentists, nutritionists, psychologists, speech therapists, among other professionals (14). The most important dental treatment needs of these patients are: surgical correction of clefts, post-surgical follow-up, oral hygiene instructions and malocclusion treatment (15).…”
Section: Introductionmentioning
confidence: 99%